Digital Influencer Marketing: How Message Credibility and Media Credibility Affect Trust and Urge to Buy among Customers in Kathmandu Valley? - Rai, Sonika; Timalsina, Prajit Kumar (SAIM Journal of Social Science and Technology, 2024)
Purpose: The purpose of this paper is to investigate the mediating role of trust in influencer posts (TR) in relation to the urge to buy (UTB) and its antecedents: perceived transparency (PT), perceived interactivity (PI), and informational value (IV) among customers in Kathmandu Valley. Design/Methodology/Approach: This paper employed a cross-sectional survey research design to gather data from 234 social media users in the Kathmandu Valley. Further, a purposive sampling method was applied to select the respondents. Furthermore, the proposed model was tested by applying Hayes Process Macro Model 4. Findings: The result reveals a significant positive influence of TR and IV on UTB. Moreover, TR partially mediates the relationship between PT and UTB, PI and UTB, and IV and UTB among customers in Kathmandu Valley. Practical Implication: By understanding the role of media and message credibility in developing trust in digital influencers’ posts, this paper could help pave the way for crafting strategies and developing marketing policies for digital marketing-based entrepreneurs. Furthermore, marketers can use this information to enhance SM users’ buying behavior through various influencer marketing campaigns. Originality: This paper is among the earliest works to underscore digital influencer marketing by understanding the mediating role of TR using social learning theory (SLT) and signaling theory as its theoretical foundations among Nepali social media (SM) users.